Beauty Standards Portrayed in the Indonesian Adaptation of 200 Pounds Beauty - Marta, Rustono Farady; Laksono, Tegar Dwi; Fernando, Joshua; Sudarji, Shanty; Maria Borges, Serilio Verdial (Universitas Islam Negeri Raden Intan Lampung, 2025)
This study aims to analyze the beauty standards in the Indonesian version of 200 Pounds Beauty (2023) using a qualitative descriptive approach and discourse analysis method developed by Sara Mills, focusing on feminism. The main objective of this research is to explore how the representation of women in the film reflects social pressures and patriarchal ideologies related to beauty. Through discourse analysis of dialogues, scenes, and socio-cultural context, this study identifies how the character Juwita experiences body-shaming and discrimination based on her appearance before and after undergoing plastic surgery. The findings indicate that the film reinforces unrealistic beauty myths, where women who meet the ideal beauty standards receive special treatment, while those who do not conform to these standards face marginalization. This research highlights the negative impact of beauty standards shaped by the media, emphasizing the importance of raising awareness about the diversity of physical appearances and boosting women's self-confidence. Thus, this study contributes to a broader understanding of the relationship between gender, beauty, and representation in the media. Keywords: Body Shaming, Feminism, Film Studies, Beauty Standards.